Pengaruh Model Pembelajaran Experiential Learning Terhadap Keterampilan Menulis Bahasa Inggris Mahasiswa PGSD Universitas Muhammadiyah Tangerang - Ratih Ayu Wulandari; Asih Rosnaningsih (Universitas Persada Indonesia YAI, 2020)
Writing is one of the productive skills that require precision and perseverance. In thelearning process, students often find it difficult to learn to write. Experiential Learning is astudent-centered learning method that emphasizes learning experience. The purpose of this studywas to determine the effect of the use of Experiential Learning model on English students' writingskills in the fourth semester of Teacher Elementary Education of University of MuhammadiyahTangerang. This research used a quantitative approach with a quasi-experimental designmethod. The instrument used in this study was a descriptive essay writing test. The resultsshowed: (1) the results of the pretest t-count 2,319> t-table 2,000 or H1 were accepted, namelythere were differences in writing skills between the control class and the experimental class, (2)the results of the posttest t-count 2,319> t-table 2,000 or H1 were accepted or there weredifferences in writing skills between control classes and experimental class after being given theExperiential Learning model. It can be concluded that by employing the Experiential Learningmodel, students can get maximum writing results because though this learning model, studentscan reflect the knowledge they have during the learning process of writing